Transition Metal Catalyzed Oxidative Cross-Coupling Reactions - Lei, Aiwen (Lecture Notes in Chemistry, 2019)
This book is a comprehensive text covering the research and development trends in the booming field of transition metal catalyzed oxidative cross-coupling reactions. Oxidative cross-coupling reaction is a new method to forming chemical bonds besides the traditional cross-coupling reactions. This book provides the answers to how this coupling reaction occurs and what its advantages are. The palladium, copper and iron catalyzed oxidative cross-coupling reactions as the main focuses of interest are described in detail. The oxidative cross-coupling reactions catalyzed by other metals and transition-metal-free oxidative coupling reactions are also introduced.This book provides a useful reference source for researchers and graduates in the field of transition metal catalyzed coupling reactions. It is also valuable to researchers working in pharmaceutical companies, fine organic chemical companies, and etc.